Les voyelles intermédiaires : des questions de normativité, usage et enseignement - Rubio, Marcela; Ibáñez, Karina (2021)
This article introduces some reflections about the phonolo gical status of vowels /e, ε, ø, œ, o, ͻ/ and how to teach them. These vocalic sounds constitute a particular instance of the French phonological system because of their articulatory and acoustic natur e, their realizations and the constrains that affect them. The starting point of research done in various relevant con texts, from acoustic phonetics (Lauret, 2007 ; Vaissière, 2011 ; Billières 2014) to phonestilistics (Léon 1993, 2011) and sociophonetics approaches (Candea & Trimaille 2015, Østby 2016). A discussion of the goals of learning is included along with a situated reflection upon our teaching context. This article also s uggests an abridged vocalic system, derived from the simplification of the degre es of openness.
L'article présente quelques réflexions sur le statut phonologique des voyelles/e, ε, ø, œ, o, ͻ/ et sur leur enseignement. Ces sons vocaliques constituent une instance particulière du système phonologique du français du fait de leur nature articulatoire et acoustique, leurs réalisations et les conditionnements qui les régissent. L'étude est partie d'un examen minutieux de recherches faites dans de différents domaines pertinents, depuis la phonétique acoustique (Lauret, 2007 ; Vaissière, 2011 ; Billières, 2014) jusqu'à la phonostylistique (Léon,1993, 2011) et la sociophonétique (Candea & Trimaille, 2015 ; Østby, 2016). La démarche inclut la discussion des objectifs d'apprentissage et une réflexion située dans notre contexte enseignant. Ce travail vise ainsi la proposition d'un système vocalique abrégé, à partir de la simplification des degrés d'aperture moyenne.
Keywords: Mid vowels; Teaching; Goals; Models; Intelligibility; Voyelles intermédiaires; Enseignement; Objectifs; Modèles; Intelligibilité^lfr